Evaluation of throwing ability after coracoid transfer in non-overhead athletes - Ryota Yokoi, DP; Takayuki Kawasaki, MD, PhD; Yuuki Hirai, DP; Hiroki Tanabe, MD; Tomohiko Tateishi, MD, PhD; Nobukazu Maki, DP; Daichi Morikawa, MD, PhD; Muneaki Ishijima, MD, PhD (JSES International, 2025)
Background: Coracoid transfer is the most common procedure for the treatment of traumatic anterior shoulder dislocations with large glenoid bone defects; however, it is rarely used for the treatment of throwing shoulders because of possible postoperative limited range of motion. This study aimed to evaluate throwing function after coracoid transfer for shoulder instability. Methods: The study included non-overhead athletes (n = 11; Bristow-Latarjet [BL] group) who suffered shoulder dislocation and underwent coracoid transfer on the dominant side of the shoulder and healthy volunteers (n = 20; C group) from the same population (overall age distribution: 18–22 years). All participants were evaluated for shoulder function including ball-throwing abilities (e.g., ball velocity and long-throw distance). In the primary analyses, we compared the maximum ball velocity and long-throw distance between the groups using the repeated 2-way analysis of variance. In secondary analyses, all other measurements were compared between the groups using the Mann–Whitney U test. Results: In the primary analysis, mean maximum ball velocity and long-throw distance in the BL and C groups were 83.5 and 87.9 km/h versus 44.8 and 54.7 m, respectively, demonstrating no significant differences between the groups. In the secondary analysis, only the range of external rotation with the shoulder at the side was significantly lower in the BL group (P = .046). Conclusion: The throwing ability after coracoid transfer in non-overhead athletes is acceptable compared to that in the matched population. Therefore, this procedure may be an option for treating traumatic anterior shoulder dislocations with large bone defects in athletes such as goalkeepers, handball, and basketball players at the recreational level.